Emotion Classification of Voice Recordings Using Deep Learning - Tumanyan, Narek T. (Изд-во НАН РА)
In this work, we present methods for voice emotion classification using deep learningtechniques. To processing audio signals, our method leverages spectral features of voicerecordings, which are known to serve as powerful representations of temporal signals. To tackling the classification task, we consider two approaches to processing spectralfeatures: as temporal signals and as spatial/2D signals. For each processing method, weuse different neural network architectures that fit the approach. Classification resultsare analyzed and insights are presented.
Keywords: Mathematical cybernetics; Computer science